Security technologies for the World Wide Web - Oppliger, Rolf (Artech House computer security series., 2003)
This newly revised edition of the Artech House bestseller brings you the most, up-to-date, comprehensive analysis of the current trends in WWW security available, with brand new chapters on authentication and authorization infrastructures, server-side security, and risk management. You also find coverage of entirely new topics such as Microsoft.NET Passport. From HTTP security, firewalls and proxy servers, cryptographic security protocols, electronic payment systems ... to public key infrastructures, authentication and authorization infrastructures, and client-side security, the book offers an in-depth understanding of the key technologies and standards used to secure the World Wide Web, Web-based applications, and Web services.